HIPPOCAMPAL MOSSY FIBER ACTIVITY EVOKES CA(2+) RELEASE IN CA3 PYRAMIDAL NEURONS VIA A METABOTROPIC GLUTAMATE RECEPTOR PATHWAY - KAPUR, A. (2001)
Mossy fiber activity can evoke Ca(2+) release from internal stores in CA3 neurons, but the physiological conditions under which this occurs and the mechanisms underlying the release are not understood. Using rat hippocampal slices we report here that short trains of mossy fiber stimulation activate group I metabotropic glutamate receptors (mGluRs) on CA3 pyramidal neurons and elicit waves of Ca(2+) release from inositol 1,4,5-trisphosphate (IP(3)) sensitive internal stores that propagate from stratum lucidum to the soma and in some cases distally out the dendrites. Activation of mGluR1,5 receptors by an agonist trans-azetidine-2,4-dicarboxylic acid (tADA) applied to stratum lucidum was also sufficient to induce waves of Ca(2+) release. This release was blocked by internal heparin, but not by dantrolene, suggesting the involvement of IP(3) rather than ryanodine receptors in not only the initial release but also in the maintenance of the propagating waves. Release could be facilitated by Ca(2+) influx through voltage-gated Ca(2+) channels, which is consistent with the known Ca(2+) sensitivity of IP(3) receptors. These results provide insight into the mechanisms and conditions of Ca(2+) release in CA3 neurons and demonstrate the powerful influence mossy fiber input can have on these neurons.